Preparation of Generic Skill Assesment (GSA) for Vocational High School Students in The Field of Refrigeration and Air Conditioning Engineering - Reza Angga Nugraha; Mumu Komaro; Supriyanto Supriyanto (Universitas Sultan Ageng Tirtayasa, 2024)
The evolving refrigeration and air conditioning engineering industry demands a workforce proficient in both technical and generic skills. Traditional competency assessment models often prioritize technical skills, leaving a gap in evaluating essential generic skills. This research introduces the Generic Skill Assessment (GSA) model, designed to holistically assess vocational school students in the refrigeration and air conditioning sector. Utilizing a mixed-methods approach, the study developed a GSA instrument validated by experts, achieving a reliability score of 0.75. Key generic skills identified include communication, teamwork, adaptability, and critical and creative thinking. The model effectively integrates these skills with technical competencies through comprehensive assessment indicators. Despite challenges such as limited academic studies, low teacher awareness of generic skills, and inadequate curriculum evaluation, the GSA model demonstrates significant positive impacts. With 83% of students well-prepared for the industry, the GSA model offers a balanced and robust framework for evaluating and enhancing students' readiness for the workforce.